THE USE OF ARTIFICIAL INTELLIGENCE TO DEVELOP EFFECTIVE PROTECTIVE CLOTHING SOLUTIONS - MYTSA, VIKTORIIA; RIABCHYKOV, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The object of the research is the development of intelligent algorithms for creating protective clothing using artificial intelligence (AI) systems. The main attention is paid to the integration of active and passive smart devices into the structure of protective materials, as well as the optimization of the process of their development using mathematical methods. Traditional methods of designing protective products are resource-intensive and do not always guarantee optimal results. The problem of ensuring effective protection against harmful factors in production environments is particularly acute. Existing AI algorithms have limitations in the correct formulation of the problem and the selection of the optimal solution. During the study, two groups of parameters were identified that affect the process of designing protective solutions. The first group determines dangerous factors (mechanical, temperature, electromagnetic, chemical, etc.), the second - the capabilities of modern protective materials and devices. Formalized approaches based on mathematical logic are proposed to optimize the process of creating protective products. An iterative algorithm with three feedback loops has been developed, which allows to increase the efficiency of the AI system. The results obtained are due to the implementation of logical-mathematical methods for formalizing design solutions. Optimization of the algorithm through feedback helps to reduce the number of iterations required to obtain an effective design to 1–3 cycles. The proposed algorithms can be integrated into industrial systems for automated design of protective products that meet modern safety requirements. Potential areas of application are the production of special clothing, personal protective equipment, as well as the development of smart systems for monitoring harmful factors in industry.